PENGARUH PENERAPAN SISTEM ADMINISTRASI E-REGISTRATION DAN E-FILING TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK (Studi Kasus pada Wajib Pajak Orang Pribadi di Kantor Pelayanan Pajak Pratama Sidoarjo Utara) - Fandi Ahmad Hasan; Afifudin Afifudin; Junaidi Junaidi (Universitas Islam Malang, 2018)
AbstractThis study was conducted to determine the effect of the application of eRegistration Administration System and e-Filing on the level of TaxpayerCompliance (Case study on Individual Taxpayers at KPP Pratama NorthSidoarjo). This type of research is explanatory research or confirmatory and usesprimary data sources by distributing 100 questionnaires to individual taxpayers asrespondents. The method used in data retrieval is incidental sampling while themethod of data analysis uses multiple linear regression analysis assisted by theSPSS program.The result of partial research shows that the application of e-Registrationand e-Filing Administration System have positive and significant influence toPersonal Taxpayer Compliance level while the research result simultaneouslyshows that the application of e-Registration and e-Filing Administration Systemalso positively influence to Compliance level Individual Taxpayer. Keywords : e-Registration, e-Filing, Taxpayer Compliance